Na electrodeposits: a new decaying mechanism for all-solid-state Na batteries revealed by synchrotron X-ray tomography. (April 2021) - Sun, Fu; Duchêne, Léo; Osenberg, Markus; Risse, Sebastian; Yang, Chao; Chen, Libao; Chen, Nan; Huang, Yongxin; Hilger, André; Dong, Kang; Arlt, Tobias; Battaglia, Corsin; et al.
Abstract: From non-destructive and cross-sectional visualization by synchrotron X-ray tomography, we suggest a novel capacity decaying mechanism of all-solid-state Na batteries built with closo-borate electrolytes caused by electrochemically generated inactive Na electrodeposits. Graphical Abstract: ga1 Highlights: Na all-solid-state batteries (Na ASSBs) were built with the closo-borate solid electrolyte. Noninvasive synchrotron X-ray tomography technique was used to study the decaying mechanisms of the cycled Na ASSBs. Markov process model was employed to describe the physicochemical meaning of the observed capacity decay. A new decaying mechanism of the Na ASSBs caused by the continuous accumulation of Na electrodeposits was proposed.